PENGUJIAN PENYIMPANGAN RADIAL DAN AKSIAL PADA MESIN BUBUT MAXIMAT V 13 DALAM RANGKA PERAWATAN PREVENTIF DI BENGKEL TEKNIK MESIN PNJ - Hasbul Hadi Aditya; Budi Yuwono (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract Measurement of lathe deviation is a crucial process that aims to accurately determine the extent to which the machine is capable of producing parts with the required precision. Deviations that occur in machines can be caused by various complex factors, including geometric errors in the machine mechanism itself, due to repeated wear and tear of components, as well as the influence of the quality of the materials used in the manufacturing process. In practice, measurement of these deviations is carried out using high-precision measuring instruments, such as measuring clocks or dial indicators, to achieve optimal accuracy. The results of this measurement will then be compared with the specifications set by the engine manufacturer as the expected performance benchmark. If there is a deviation that exceeds the specified specification limits, then the machine may have to be repaired or readjusted immediately so that it can operate optimally again and produce products with the desired level of precision. Thus, measurement of lathe deviation becomes a critical step in the manufacturing process that guarantees the quality and accuracy of the products produced, as well as supports efforts to achieve efficiency and competitive advantage in the manufacturing industry. Abstrak Pengukuran penyimpangan mesin bubut merupakan langkah penting untuk menentukan tingkat presisi mesin dalam menghasilkan bagian-bagian produk. Penyimpangan ini dapat disebabkan oleh berbagai faktor seperti kesalahan geometris pada mekanisme mesin, keausan komponen yang sudah digunakan, atau kualitas bahan baku. Pengukuran dilakukan dengan alat ukur presisi tinggi seperti jam ukur atau indikator dial untuk mencapai akurasi optimal. Hasil pengukuran dibandingkan dengan spesifikasi yang ditetapkan oleh produsen sebagai tolak ukur performa yang diharapkan. Jika terjadi penyimpangan melebihi batas spesifikasi, mesin harus segera diperbaiki atau disetel ulang agar dapat beroperasi dengan optimal dan menghasilkan produk yang sesuai presisi. Dengan demikian, pengukuran penyimpangan mesin bubut menjadi langkah kritis dalam manufaktur untuk menjamin kualitas produk, efisiensi, dan keunggulan kompetitif di industri manufaktur.